Menumbuhkembangkan Motivasi Belajar Untuk Menggapai Cita-Cita Siswa Di SMAN 4, SMKN 7, SMKN 8 Dan SMKS Muhammadiyah 1 Kota Padang - Hastini, Lasti Yossi; Chaeroel, Lucy; Octavera, Sari; Anggraini, Dina; Abdilla, Mohammad; Riski, Tri Rachmat; Surianti, Fadila; Rismananda, Rachyta (LPPM Universitas Dharma Andalas, 2025)
The motivation of senior high school students in class XII of Padang city is still relatively low and the reinforcement of certain subject concepts according to the independent curriculum is also lacking. This has an impact on the low academic achievement of students and the number of graduates accepted at State Universities each year is still not optimal. The purpose of community service activities is to increase the number of senior high school graduates in class XII of Padang city accepted at various State Universities each year. The method of implementing the activity is in accordance with the solution offered in the form of lecture, discussion and counseling methods. The solution offered to senior high school students in class XII of Padang city provides counseling on learning motivation and reinforcement of certain subject concepts according to the independent curriculum. This solution is expected to have an impact on the number of senior high school graduates in class XII of Padang city accepted at various State Universities each year increasing by around more than 80%. Learning motivation is intrinsic and extrinsic and is related to the learning process, making students more enthusiastic in learning. Reinforcement of certain subjects is a positive response given by teachers to students in the learning process as feedback so that students can maintain or improve good behavior.